Factors determining behavioral intentions to use Islamic crowdfunding platform in times of Covid-19 in Indonesia: Evidence from TAM approach - Sulaeman Sulaeman (Jurnal Ekonomi & Keuangan Islam, 2021)
Purpose – The research paper aims to test empirically the behavioral intention of crowdfunders to use the Islamic crowdfunding platform model based on the theory of the Technology Acceptance Model (TAM).Methodology – The study used primary data that are collected by using the online survey questionnaires and then the analysis is conducted using partial least squares (PLS).Findings – The empirical evidence shows that the perceived usefulness (PU) has a significant positive impact on the behavioral intention (BI) of crowdfunders to use Islamic crowdfunding platform. Furthermore, the perceived ease of use (PEOU) also has a significant and positive relationship as well as direct effect with perceived usefulness (PU) of crowdfunders to use the online platforms. Meanwhile, that perceived ease of use (PEOU) has an insignificant relationship with the behavioral intention (BI) of crowdfunders to use the Islamic crowdfunding platform during the Covid-19 pandemic in Indonesia. Practical implications – The present study has implications for Islamic FinTech companies to provide investment platforms for crowdfunders and financial services for micro small and medium-sized enterprises (MSMEs) during the pandemic of Covid-19.Originality – The finding of this study will contribute to the existing literature in the areas of Islamic FinTech especially on the factors influencing behavioral intentions to use the Islamic crowdfunding platform in times of Covid-19 in Indonesia.